2017
DOI: 10.1016/j.cub.2016.10.047
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Body Plan of Indirect Developing Hemichordates Develops by Adding a Hox-Patterned Trunk to an Anterior Larval Territory

Abstract: Many animals are indirect developers with distinct larval and adult body plans [1]. The molecular basis of differences between larval and adult forms is often poorly understood, adding a level of uncertainty to comparative developmental studies that use data from both indirect and direct developers. Here we compare the larval and adult body plans of an indirect developing hemichordate, Schizocardium californicum [2]. We describe the expression of 27 transcription factors with conserved roles in deuterostome ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(132 citation statements)
references
References 39 publications
8
112
0
Order By: Relevance
“…Tsuchimoto and Yamaguchi () showed that the Pj‐dlx domain extends from the apical plate to the whole vestibule. Even in the indirect‐developing hemichordate Schizocardium californicum , the anterior genes, such as dlx, rx , and six3/6 , are expressed in the apical plate of larvae (Gonzalez et al, ). In our analyses, Pj‐sfrp1/5 domain was located in the apical/animal pole region (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuchimoto and Yamaguchi () showed that the Pj‐dlx domain extends from the apical plate to the whole vestibule. Even in the indirect‐developing hemichordate Schizocardium californicum , the anterior genes, such as dlx, rx , and six3/6 , are expressed in the apical plate of larvae (Gonzalez et al, ). In our analyses, Pj‐sfrp1/5 domain was located in the apical/animal pole region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A). Expression of gbx and en in the posterior collar ectoderm is conserved in S. californicum (Gonzalez et al, ). In P. japonica , Morino et al () indicated that Pj‐pax2/5/8 is expressed in ectoderm overlying the spine rudiments, and we confirm this (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, Hox genes are not expressed in the proboscis and head of Notospermus nor in lophophores of Phoronis and Lingula. This anterior Hox-free region is also found in juvenile amphioxus 37 , hemichordates 38 , arthropods 39 , nemerteans 40 and annelids 41 , suggesting that the absence of Hox gene expression at the anterior end is a common adult body plan for all bilaterians.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 94%
“…The sequence of the Schizocardium californicum polyketide synthase was provided by Chris Lowe of Hopkins Marine Station at Stanford University, and is from a previously described transcriptome assembly (Gonzalez et al, 2017). …”
Section: Methodsmentioning
confidence: 99%